Telaah Sanad dan Matan Hadis Iftirāq al-Ummah - Mardiyah; Alma’arif; Abdul Wahab; Sari Haryati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
The Hadith of Iftirāq al-Ummah states that the Muslim community will split into seventy-three sects, with only one group known as al-Firqah al-Nājiyah attaining salvation. This study aims to critically analyze the chain of transmission (sanad) and the text (matan) of this hadith, as well as to examine its contemporary theological implications, particularly concerning the understanding of the Firqah Nājiyah concept within the framework of Religious Moderation. The methodology applied includes takhrij and naqd al-ḥadīth (hadith criticism), enriched by a comparative study of the perspectives of classical theologians (mutakallimūn) and contemporary Indonesian scholars. The research findings reveal that this hadith possesses a strong sanad (ṣaḥīḥ li-ghayrihi) due to support from various corroborative transmissions (mutāba'āt). However, the matan specifically the threatening phrase